N-heterocyclic carbene catalysis exploiting oxidative imine umpolung for the generation of imidoyl azoliums - Das, Tamal Kanti; Madica, Krishnaprasad; Krishnan, Jagadeesh; Marelli, Udaya Kiran; Biju, Akkattu T. (Journal of Organic Chemistry, 2020)
Although NHC-catalyzed umpolung of imines are known, the related reactions under oxidative conditions are limited. Described herein is the two-step process involving the initial formation of aldimines from the corresponding aldehydes and 2-amino benzyl alcohols followed by NHC-catalyzed cyclization proceeding via the imidoyl azoliums under oxidative conditions. The reaction allowed the synthesis of trifluoromethylated 3,1-benzoxazines in good yields and broad scope. The role of NHC in the intramolecular cyclization and preliminary mechanistic experiments are also provided.